The Medal of Honor : The Evolution of America's Highest Military Decoration - Mears, Dwight S. (Book collections on Project MUSE., 2018)
"In The Medal of Honor, Dwight Mears takes a comprehensive look at the historical, legal, and policy underpinnings of the Medal of Honor (often referred to as the Congressional Medal of Honor), America's highest military decoration for valor in combat. In recent years the medal's eligibility criteria have been largely standardized among all military services. Prior to 1963, however, different criteria for the Medal of Honor existed between the Army and the Navy due to different controlling statutes and policies as well as divergent perceptions about the award's purpose. The early twentieth century was a turning point for both military services, as the period saw the codification of legislation designed to keep the award from undeserving recipients, largely in reaction to perceived legal and policy errors or omissions of the past. The medal's continued statutory and policy evolution has produced a number of contemporary concerns, including perceptions that bureaucratic and legislative barriers have effectively pushed the decoration out of reach of deserving service members, and that remedies were necessary to correct for past discrimination that resulted in the unfair downgrade of many awards in earlier conflicts. Existing literature on the Medal of Honor avoids in-depth analysis, preferring instead to focus on the most deserving recipients in different periods of US history. Due to its depth and comprehensiveness, The Medal of Honor is likely to be the definitive book on the subject."--Provided by publisher